138 Mask or Nasal Tube to Provide Positive Pressure Ventilation (PPV) to Preterm Infants in the Delivery Room (DR)-The Mont Trial. (October 2012) - Kamlin, COF; Schilleman, K; Dawson, JA; Lopriore, E; Donath, S; Schmoelzer, GM; Walther, FJ; Davis, PG; Pas, AB te
Abstract : Background: For initial PPV a face mask is used, but obstruction and leak often occurs. A nasal tube is an alternative interface in the DR to provide PPV. Its safety and efficacy have not been tested in a large RCT in extremely preterm infants. Objective: To determine whether a single nasal tube is more effective than face mask during the stabilisation of infants born between 24 and 29 weeks. Design and methods: An RCT performed in Melbourne and Leiden. Infants were randomized immediately prior to birth to receive PPV using a T-piece with either a nasal tube or round mask. Resuscitation guidelines were standardised. Criteria for intubation: cardiac compressions, apnea, CPAP >7cmH2 O and FiO2 >0.4. Primary outcome: intubation in the first 24 hours from birth. Results: In total 368 infants were randomized. Baseline variables, primary and secondary outcomes were similar (table ). Conclusions: In infants < 30 weeks gestation receiving PPV in the DR, there were no differences in short term outcomes using the nasal tube compared to the face mask.